If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2x + 1) = 0 Reorder the terms: 2x(1 + 2x) = 0 (1 * 2x + 2x * 2x) = 0 (2x + 4x2) = 0 Solving 2x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(1 + 2x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {0, -0.5}
| .8-4(y-1)=.2+3(4-y) | | 1/3*-3/2 | | G(k)=12-5k | | -5=-2+2y | | 4y^2+32y+64=0 | | V(squared)+x=w(squared) | | (2*x)-sin(2*x)=10 | | 13a+8+8a+2= | | 2=2*-5-1 | | 3(2x+4)-4x=5(3x+20) | | 9x-8y=-3 | | -4x-2+7x+12= | | x+(x*.15)=27.38 | | -m+5-8m+16= | | y^2-2y-90=0 | | 5p^2+5=465 | | 23=5y-4(-2+2y) | | 5y+12-9y-7= | | 2x-61+y=180 | | 2x^2+6x+0=0 | | (12-X)/4=5 | | 4n-26+27=2n+17 | | 23=5(4-x)-4x | | 10b+4b-b+2+b+6= | | 4-14=14 | | -3(-1+3w)=-(-13+10w) | | 135/x=85/310 | | 8q+2q+7q-5= | | -(-7x+9)+(3x-1)=0 | | 5(17p+15)-16=6(14p+7) | | 2x+3y+12+3x+6y-7= | | -6(10h-20)=-18h-6 |